Implementation facilitators and barriers of stress first aid to protect mental health of frontline health care workers during the COVID-19 pandemic: a qualitative study - Shreya S. Huilgol; Lu Dong; Nabeel Qureshi; Kathryn Bouskill; Lisa S. Meredith; Courtney Gidengil (BMC Health Services Research)
Abstract Background The COVID-19 pandemic has taken a toll on frontline health care workers (HCWs), leading to poor mental and physical well-being. We conducted a large, cluster randomized controlled trial to implement an adapted Stress First Aid (SFA) intervention to support HCW well-being using a train-the-trainer (TTT) approach for rapid deployment in the United States and collected qualitative data through interviews to understand implementation. The goal of this study is to understand barriers and facilitators to deploying SFA using a TTT model, with particular emphasis on the acceptability, uptake, and barriers from the implementation. Methods We conducted seven individual and seven group semi-structured qualitative interviews with 28 trainers (i.e., site champions) who delivered SFA training to their local HCWs from Spring 2021 to Winter 2022 in hospitals and health care centers within the United States. We utilized both inductive and deductive approaches to coding transcripts. All transcripts were coded in Dedoose. We used the Consolidated Framework for Implementation Research (CFIR) to rigorously assess implementation experiences. Results Site champions highlighted leadership buy-in, protected time and incentives, and teams as implementation facilitators, while implementation barriers included unhelpful training materials and content, time constraints and scheduling difficulties, and pandemic-related factors, such as COVID-19 surges. SFA implementation processes varied: some champions had virtual SFA presentations, while others held informal discussions about SFA material in person. Champions also differed on their perceptions of SFA sustainability: some indicated it would be difficult to sustain SFA in their organization due to limited structure and time, while others stated they would continue to utilize it. Conclusion Limited research has examined the implementation of HCW well-being interventions using a TTT approach in a changing environment. Site champions were able to implement SFA during a period of rapid and frequent change and shared several implementation facilitators and barriers related to the SFA intervention. In the future, addressing the implementation barriers proactively and prioritizing the implementation facilitators may prove to be useful for large-scale interventions implemented during disease outbreaks and pandemics.